2012-2013 University of Southampton Poole Harbour Crassostrea gigas transect and settlement panel records ... : 2013 University of Southampton Poole Harbour Magallana gigas transect and settlement panel records ... - University of Southampton (The Archive for Marine Species and Habitats Data (DASSH), 2024)
The work carried out so far highlights Poole Harbour as being an anomaly in the apparent steady progressive development of Pacific oyster populations around the coast, in that there is an obvious source of larvae but little successful settlement. The mechanisms which are ‘dampening down’ expected settlement appear to include at least one physical factor but it is likely that this is moderated by biological factors such as competition for settlement space and predation. Further work is required to establish which biological factors may be modifying recruitment success and whether recruitment is moderated during the larval stage or post metamorphosis. if the dominant controlling factor(s) act before oyster settlement it is most likely water temperature that controls the naturalised population, however top-down control by predators could be significant if oysters are surviving metamorphosis. ... : Part of MSFD NNS baseline data collation project (Hughes, E., Wood, C.A., Arnold, M., Bishop, J.D.D., Griffiths, C., Sewell, J., and Lear, D. (2016) Collating baseline invasive non-indigenous species data for MSFD reporting. Defra report ME5223. 59pp.). Subset of a dataset as records were only pulled for a selection of INNS. ...